Finding of a mass on the mitral valve in a patient on chronic dialysis - Vasil Papestiev, MD, PhD; Marjan Shokarovski, MD; Nikola Lazovski, MD; Nadica Mehmedovic, MD; Valentina Andova, MD, PhD; Gordana Petrushevska, MD, PhD; Ljubica Georgievska-Ismail, MD, PhD (Radiology Case Reports, 2025)
Myxomas are cardiac neoplasms that are most commonly located in the left atrium, usually arising from the vicinity of the fossa ovalis. However, there have been cases, although very rarely, of valvular myxoma. A cardiac mass found incidentally on echocardiography can present a challenge in particular if asymptomatic or found in an unusual location. We present the case of a 58-year-old male with kidney disease treated with chronic dialysis, referred to the cardiology clinic because of an incidental finding of a mitral valvular mass on routine transthoracic echocardiography. Although this lesion was initially misdiagnosed as native valvular endocarditis with vegetation, a series of clinical and radiological investigations led to the preoperative diagnosis of possible papillary fibroelastoma or calcified thrombotic mass. Given the increased risk of embolization due to the mass being mobile and greater than 1 cm in size, the patient was referred to cardiac surgery. Excision of the mass without mitral valve replacement was performed. Histopathological findings of the mass revealed the existence of a cardiac myxoma. In such cases of a mitral valve mass, multimodality imaging should have of high priority to achieve an accurate diagnosis. Although a definitive diagnosis can only be established after surgical excision of the mass and histopathological confirmation, it is very important to consider a differential diagnosis of mitral valve myxoma in any patient with an unexplained mitral valve mass.